2013
DOI: 10.3144/expresspolymlett.2013.70
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and properties of Se nanowires intercalated polyaniline/Se nanocomposites

Abstract: Abstract. Present work reports novel synthesis of Polyaniline (PANI)/Se nanocomposites. Se nanowires are prepared from SeO 2 under assistance of vitamin C and polyaniline is synthesized through chemical oxidation. The effect of composition of Se nanowires on the properties of polyaniline was investigated and five orders increase in conductivity after doping has been observed. The electrical properties of nanocomposites show that conduction is through hopping process due to the wide range of localized states pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…15,23,24 The bands at 1732.69 cm À1 correspond to an out-of-plane C-H bending vibration of carboxyl groups. 25,26 Interestingly, the peaks aer graing shied to a higher wave number region indicating the formation of crosslinked hydrogel. The bands at 732 cm À1 correspond to an outof-plane C-H bending vibration of para-disubstituted rings.…”
Section: Characterization Of Synthesized Hydrogelsmentioning
confidence: 99%
“…15,23,24 The bands at 1732.69 cm À1 correspond to an out-of-plane C-H bending vibration of carboxyl groups. 25,26 Interestingly, the peaks aer graing shied to a higher wave number region indicating the formation of crosslinked hydrogel. The bands at 732 cm À1 correspond to an outof-plane C-H bending vibration of para-disubstituted rings.…”
Section: Characterization Of Synthesized Hydrogelsmentioning
confidence: 99%
“…Conducting form of PANI is described by band at 1237 cm -1 [10,46]. The bands at 796 and 1731 cm -1 were corresponding to an out-of-plane bending vibration of C-H on para-disubstituted rings and carboxyl groups, respectively [10,47,48]. It has been reported that the band at 1110 cm -1 to be a measure of the degree of the delocalization of electrons and is also revealing of high conductivity.…”
Section: Ftir Spectroscopymentioning
confidence: 99%
“…The conduction mechanism in our investigated nanocomposites results from the hopping process of charge carriers as a charge transport passes into the polymer in conducting polymer systems, a mechanism of transport is also similar to this in amorphous semiconductors (hopping carrier) (Caseri, 2000;Shumaila et al, 2013). The agent defining the conductivity is the transport movement, along with the carrier concentration.…”
Section: X-ray Diffraction (Xrd) Analysismentioning
confidence: 75%